Current treatments for renal failure due to multiple myeloma - Kastritis, E.; Terpos, E.; Dimopoulos, M.A. (Expert Opinion on Pharmacotherapy, 2013)
Introduction: Renal impairment (RI) is a common complication of symptomatic myeloma; 20-40% of newly diagnosed patients present with moderate or severe RI and 10% of them may require dialysis. Immediate initiation of specific antimyeloma therapy is crucial in order to improve RI. Areas covered: There has been a significant improvement in the outcome of patients with RI over the past 15 years. The authors review current data on the role of antimyeloma therapy on the improvement or resolution of RI and the importance of novel regimens, especially those based on bortezomib. IMiDs-based regimens, conventional chemotherapy and high-dose therapy is also reviewed. The role of extrarenal free light chain removal, by means of plasma exchange or extended hemodialysis with the use of high cutoff dialysis membranes, is also discussed. Expert opinion: Bortezomib/dexamethasone-based regimens are the preferred regimens for most patients with multiple myeloma (MM) who present with RI, especially for newly diagnosed patients; however, other novel agents (thalidomide, lenalidomide) in combination with dexamethasone may also improve RI in several patients. Further investigation is needed for the clarification of the role of plasma exchange or extended high cutoff dialysis. Carfilzomib, which was recently approved, may also be a treatment choice for selected patients with relapsed MM and RI. © 2013 Informa UK, Ltd.
Keywords: bortezomib; Dexamethasone; Dialysis; Lenalidomide; Plasma exchange; Thalidomide